1999
DOI: 10.1007/s003300050625
|View full text |Cite
|
Sign up to set email alerts
|

Accessory cardiac bronchus: 3D CT demonstration in nine cases

Abstract: Accessory cardiac bronchus (ACB) has been described mainly as isolated case reports in the literature. We report nine consecutive cases of ACB, which occurred in five males and four females and were detected in 11,159 routine spiral CT examinations of the chest, performed between 1994 and 1998. Frequency of the anomaly was 0.08 %. Accessory cardiac bronchus originated from the intermediate bronchus in eight cases and from the right main bronchus in one case. Mean largest diameter of ACB was 8.7 mm (range 4.0-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 8 publications
(5 reference statements)
0
24
0
4
Order By: Relevance
“…10,[13][14][15] It presents with a blind distal end or shows a ventilated lobule. 14,15 In a study of 11,159 spiral chest CT examinations, 9 cases of accessory cardiac bronchus were found, a frequency of 0.08%. 14 Accessory cardiac bronchus is asymptomatic and incidentally discovered, but recognition of this anomaly is important because recurrent infection or hemoptysis can develop in a small percentage of patients.…”
Section: Accessory Cardiac Bronchusmentioning
confidence: 98%
“…10,[13][14][15] It presents with a blind distal end or shows a ventilated lobule. 14,15 In a study of 11,159 spiral chest CT examinations, 9 cases of accessory cardiac bronchus were found, a frequency of 0.08%. 14 Accessory cardiac bronchus is asymptomatic and incidentally discovered, but recognition of this anomaly is important because recurrent infection or hemoptysis can develop in a small percentage of patients.…”
Section: Accessory Cardiac Bronchusmentioning
confidence: 98%
“…These findings are in concordance with our results (75% displace type, 50% of them are pre-eparterial). Ghaye et al (1999), studied on 11159 images by MDCT with 3D volumetric display and shaded-surface display, and detected 9 cases with accessory cardiac bronchus (0.08%). They reported that accessory cardiac bronchus originated from the intermediate bronchus in 8 cases and from the right main bronchus in 1 case.…”
Section: Discussionmentioning
confidence: 99%
“…The left upper lobe bronchus is hyparterial because it is below the left pulmonary artery. If the displaced type tracheal bronchus is proximal to the origin of the superior lobar bronchus, it is called as preparterial in right and eparterial or pre-hyparterial in left; if it is distal to the origin of the superior lobe bronchus, it is known as posteparterial in right and hyparterial in left (McGuinness et al, 1993;Ghaye et al, 1999Ghaye et al, , 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Most cardiac bronchi end blindly, but some develop into a series of small bronchioles ending in vestigial bronchiolar parenchyma or a ventilated lobulus [8,10]. Like most other congenital airway abnormalities, cardiac bronchi are typically asymptomatic and are found incidentally on CT examinations, but hemoptysis and recurrent pneumonia may develop in a few patients [8,10].…”
Section: Heidinger Et Almentioning
confidence: 97%